PELAKSANAAN PROMOSI BATIK PADA TOKO BATIK SANG SURYA PEKANBARU - SOFYAN, RUDI; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine how the implementation of sales promotion ( Advertising , sales promotion , personal selling ) simultaneously or partially in order to achieve the sales target of the Sang surya Pekanbaru batik shops .As for the population in this study is the consumer of the Sun batik shop Pekanbaru Pekanbaru , with sampling totaling 89 people by using Slovin formula . Search procedure is performed based on random sampling of respondents . The research data is the primary data , the questionnaire as a research instrument , data analysis is descriptive analysis , as it also uses descriptive quantitative analysis that uses sitem calculations and using SPSS version 20 .promotion of information flow in one direction or persuasion made to direct the activities of a person or organization that created the exchange in a pemasaran.Promosi is one part of the marketing mix is crucial implemented by companies in marketing products or services that aim to get the maximum profit mungkin.Promosi are attempts by marketers to inform and remind the people in the target market about the products ,Keywords :. Promotion mix (Advertising, Sales Promotion and Personal Selling